A new flat-plate radiative cooling and solar collector numerical model: Evaluation and metamodeling. (1st July 2020) - Vall, Sergi; Johannes, Kévyn; David, Damien; Castell, Albert
Abstract: Radiative cooling is a renewable technology that can complement or partially replace current cooling technologies. Coupling radiative cooling with another technology, such as solar collection could foster its development and implementation in the market. Therefore, a numerical model capable to simulate the behavior of a coupled radiative cooling and solar collection system is developed and presented in this paper. The model is validated with experimental data for both solar collection and radiative cooling operation, and a sensitivity analysis is performed in order to determine the most influencing parameters. Results show the potential of the device to perform the double functionality: solar thermal collector and radiative cooler. As expected the heating power ( 17.11 k W h / m 2 ) is one order of magnitude higher than the cooling one ( 2.82 k W h / m 2 ). The sensitivity analysis determined the existence of an important role played by 5 parameters (air gap thermal conductivity, absorptivity/emissivity of the radiator at 7–14 μm wavelength range, transmissivity of the cover material 2 at 7–14 μm wavelength range, water inlet temperature, and water inlet flow) and 4 combinations of these parameters in the radiative cooling mode. Highlights: A numerical model of a combined solar collector and radiative cooler is presented. A sensitivity analysis determines the most influencing parameters. The potential of the device to perform the double functionality is demonstrated.